Optimization and Characterization of Naringenin Transfersomes with Simplex Lattice Design and Anti-Aging In Vivo Study - Yuliana, Sinta; Kuncahyo, Ilham; Harmastuti, Nuraini (Jurnal Mandala Pharmacon Indonesia, 2025)
Naringenin acts as an antioxidant, neutralizing free radicals that are present in the atmosphere and which are responsible for a number of adverse effects on the skin, including photoaging, the formation of wrinkles, and a loss of radiance. The objective of this study is to determine the effect of varying phospatidilcholine, cholesterole, and tween 80 on the characteristics of naringenin transfersome and their efficacy as anti-aging agents. A total of 14 naringenin transfersome formulas were subjected to testing using the Design-Expert application, using simplex lattice design method. The particle size, polidispersity index, zeta potential, and % Entrapment efficiency were evaluated. Subsequently, the optimal formula was subjected to in vivo anti-aging testing. The characterization results obtained for the PSA test indicate a range of values between 70 and 90 nm for the naringenin transfersomes. The % Efficiency of Absorption test yielded results between 80 and 92%, while the PDI test exhibited a range close to. The value of zero is obtained for the zeta potential, and the results are distant from this value. The optimum formula, as predicted by the Simplex lattice design method, provides results for the characterization test that are in close alignment with the actual outcomes.